2021
DOI: 10.3892/mmr.2021.12195
|View full text |Cite
|
Sign up to set email alerts
|

An increase in elastogenic components in the placental villi of women with chronic venous disease during pregnancy is associated with decreased EGFL7 expression level

Abstract: Chronic venous disease (CVD) is the response to a series of hemodynamic changes in the venous system and the onset of this disease is often triggered by pregnancy. Placental tissue is particularly sensitive to the characteristic changes which occurs in venous hypertension. In this regard, changes in the extracellular matrix (ECM), that occur to adapt to this situation, are fundamental to controlling elastogenesis. Therefore, the aim of the present study was to analyze the changes that occur in the mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…For the first time, we have demonstrated significant changes in tissue expression of critical cell to ECM (ILK) and cell to cell (e-cadherin, cadherin 7 and cadherin-9) components in placentas of women with CVD. These results are in consonance with our previous studies that showed that CVD is associated with a set of changes in the placenta in the ECM [7,16] and cell behavior [13,17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For the first time, we have demonstrated significant changes in tissue expression of critical cell to ECM (ILK) and cell to cell (e-cadherin, cadherin 7 and cadherin-9) components in placentas of women with CVD. These results are in consonance with our previous studies that showed that CVD is associated with a set of changes in the placenta in the ECM [7,16] and cell behavior [13,17].…”
Section: Discussionsupporting
confidence: 93%
“…In this line, we have demonstrated that maternal venous dysfunction also induces multiple abnormalities and damage in the placenta, evidencing an increase of hypoxic markers and enhanced apoptosis [13], markers of oxidative stress [14] and altered angiogenesis and lymphangiogenesis [15]. Moreover, we also found that CVD is associated with changes in the placental composition [7,16] and signaling [17], suggesting that this condition drives detrimental modifications in the placental structure and functioning, probably representing a unique pathophysiological feature in response to the venous dysfunction.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…All of these molecular variations may also be related to a switch in lipidomic profiling in the placenta of women with CVeD [269]. Finally, we observed that profound remodeling affects the placental tissue, with dysregulation of collagen and elastic fibers, including an increase in type III collagen, matrix metalloprotease 9 (MMP-9), and elastogenic processes with a decrease in EGFL7 expression [270,271]. Currently, the impact of CVeD in maternal and fetal well-being is starting to be elucidated.…”
Section: Chronic Venous Disease Clinical Manifestations and Repercuss...mentioning
confidence: 99%
“…The last steps were dehydration in 96% alcohol for 5 min, dehydration in 100% alcohol for 5 min, xylol clearance for 10 min and Cytoseal™ mounting (Epredia™ 8310-4, Thermo Fisher Scientific A., Waltham, MA, USA). The use of this technique evidences the presence of the elastic fibers in a brown color [16].…”
Section: Orcein Methodsmentioning
confidence: 90%